The fight of your life : manning up to the challenge of sexual integrity - Clinton, Timothy E., 1960-; Laaser, Mark R. (Shippensburg, PA : Destiny Image Publishers, Inc., 2015)
"There's a war going on for the souls of men. It's reached epic levels and is threatening the very fabric of generations--grandfathers, dads, sons, and grandsons. This war is affecting you and your family. Landmines planted strategically by the enemy that are knocking our men out, destroying their souls, ruining their futures, causing destructive marriage issues, jeopardizing relationships, and taking our sons and daughters captive! The war is an all-out attack on the purpose and pleasure of sexuality as God designed it. The Fight of Your Life offers weapons that help you overcome sexual addiction, resist the danger of pornography, enjoy healthy sexuality, and save your marriages, relationships, and families from the enemy's assault. To win the war, you must fight the battles. Don't give up. Don't lose hope. And don't think for a moment that you have disqualified yourself from the fight. You have not failed too many times--you can still win!"--
Foreword -- The fight of your life -- Casualties of war -- Sex on the brain -- Our plastic brain -- Building blocks of strongholds -- The heart of the matter -- The game changer -- The paradox of grace: when weakness is strength -- What good is God? (Do you want to be healed?) -- Can you handle the truth? -- Accountability: why we need it to work -- Yada, yada, yada! -- Taking back the ground and holding it -- Healing your marriage -- Fighting for a legacy: passing freedom to the next generations -- Your halftime speech: living the dream (To love and be loved) -- Appendix: Sexual integrity inventory -- Resources.
Includes bibliographical references (pages 233-[237]).
Keywords: Sex -- Religious aspects -- Christianity; Pornography -- Religious aspects -- Christianity; Sex addiction -- Religious aspects -- Christianity; Marriage -- Religious aspects -- Christianity; Interpersonal relations -- Religious aspects -- Christianity; Intimacy (Psychology) -- Religious aspects -- Christianity